Notary Profession and Code Of Ethics In The Process Of Making A Deed Of Establishment Of A Limited Liability Company - Christine Christine; Gunardi Gunardi (Publikasi Indonesia, 2023)
A notary in business, especially in the growth of a Limited Corporation as a legal institution, is considered necessary. Therefore, the corporation can also gain legal protection besides obeying the rules. The presence of an authentic act- a legal product released by a notary- supports the law concept that becomes the source of justice. The procedure is the key to the established law; without proper procedure based on the established law and correct procedure based on established rules and regulations, the whole system will fail; therefore, the procedure has a vital role in maintaining a system. In founding a Limited Corporation, the role of a notary becomes the link of all procedures, especially after establishing the legal institution Administration Sistem in 2000 with the decree of the Minister of Law and Human Rights of the Republic of Indonesia number M01.HT.01.01. The year 2000 about The Enforcement of Legal Institution Administration Sistem in General Directorial of General Law Administration of Law and Human Rights Department Republic of Indonesia. The legal Institution Administration System was established to replace the ineffective manual system in founding limited Corporation Legalization. Many reasons still support manual system use, although it is against the former rule mentioned if the manual system is no longer usable.